Poly(lactic acid) blends in biomedical applications - Saini, P.; Arora, M.; Kumar, M.N.V. Ravi (Advanced drug delivery reviews, 2016)
Poly(lactic acid) (PLA) has become a “material of choice” in biomedical applications for its ability to fulfill complex needs that typically include properties such as biocompatibility, biodegradability, mechanical strength, and processability. Despite the advantages of pure PLA in a wider spectrum of applications, it is limited by its hydrophobicity, low impact toughness, and slow degradation rate. Blending PLA with other polymers offers a convenient option to enhance its properties or generate novel properties for target applications without the need to develop new materials. PLA blends with different natural and synthetic polymers have been developed by solvent and melt blending techniques and further processed based on end-use applications. A variety of PLA blends has been explored for biomedical applications such as drug delivery, implants, sutures, and tissue engineering. This review discusses the opportunities for PLA blends in the biomedical arena, including the overview of blending and postblend processing techniques and the applications of PLA blends currently in use and under development. [Display omitted]